Hybrid scheduling and dual queue scheduling - Mahmood, Ahmad Kamil (2009)
Multiprogramming computer systems execute multiple programs concurrently. An objective of multiprogramming is to optimize resource utilization. Efficient resource utilization is achieved by sharing system resources amongst multiple users and system processes. Optimum resource sharing depends on the efficient scheduling of competing users and system processes for the processor, which renders process scheduling an important aspect of a multiprogramming operating system. As the processor is the most important resource, process scheduling, which is called CPU scheduling, becomes all the more important in achieving the above mentioned objectives. Many algorithms have been developed for the CPU scheduling of a modern multiprogramming operating system. Our research work involves the design and development of new CPU scheduling algorithms (the Hybrid Scheduling Algorithm and the Dual Queue Scheduling Algorithm) with a view to optimization. This work involves a software tool which produces a comprehensive simulation of a number of CPU scheduling algorithms. The tool's results are in the form of scheduling performance metrics. Â© 2009 IEEE.